Development of antimicrobial oxidized cellulose film for active food packaging. (15th February 2022) - Gao, Pangye; Cha, Ruitao; Luo, Huize; Xu, Yiran; Zhang, Pai; Han, Lu; Wang, Xiaohui; Zhang, Zhenlin; Jiang, Xingyu
Abstract: Foodborne diseases caused by bacteria have aroused ongoing concerns for food safety. Most existing packaging plastics bring pollution and potential toxicity. Here antimicrobial dialdehyde cellophane (DACP) was developed by periodate oxidation. The structure, mechanical properties, optical properties, and barrier properties of DACP were characterized. The antimicrobial activity of DACP against four Gram-positive bacteria was studied. The packaging effect of DACP for food with high water content was evaluated, including strawberry and tofu. The antimicrobial activity of DACP improved with increased aldehyde content. Compared with the polyethylene film and cellophane, our DACP exhibited excellent antimicrobial effect and extended the shelf life of food significantly, which shows promising prospects in food packaging. Graphical abstract: Unlabelled Image